Access to justice in environmental matters : a socio-economic analysis (Eleven International Publishing : Metro, 2013)
This book examines how to push forward access to justice in environmental matters in the EU. The authors analyze four options from a Law and Economics and Law and Society perspective. In addition, they include an empirical study of the consequences of the four options in Latvia, the United Kingdom and Germany. The goal of the book is twofold: (a) to highlight the differences between the four options from an economic perspective and (b) to investigate to what extent the absence of an EU-wide regime for access to justice in environmental matters is disadvantageous. This book is unique as for the first time, an in-depth socio-economic analysis of access to justice is given. The book is of interest to EU environmental lawyer and policymakers.